Diversidade de Chiroptera do quaternário de Serra da Mesa (GO) com ênfase na morfologia do aparelho mastigatório - Fracasso, Maria Paula de Aguiar (2003)
Evaluate the taxonomic diversity of fossil bats (Chiroptera) from the region of the Serra da Mesa in the State of Goias, Central Brazil. Quaternary fossils were obtained from four limestone caves, namely Igrejinha, Carneiro, Nossa Senhora Aparecida, and ltambé. The taxonomic identification of the fragments was based on a original comparative study of the masticatory apparatus of extant bat species. A total of 431 fragments were identified, comprising 28 species: Anoura cf. geoffroyi, Artibeus (Artibeus) sp., Carollia sp., Chrotopterus auritus, Desmodus rotundus, Desmodus sp., Emballonuridae sp. indet., Eptesicus Histiotus, Glossophaga sp., Lionycteris spurrelli, Lonchorhina aurita, Micronycteris megalotis, Mimon bennetti, Mimon crenulatum, Molossidae sp. indet., Myotis sp., Natalus straminaeus, Phyllostomus discolar, Phyllostomus hastatus, Platyrrhinus sp., Platyrrhinus Uroderma, Pteronotus davyi, Pteronotus parnelli, Sturnira sp., Tonatia bidens, Tonatia silvicola, Tonatia sp., Trachops cirrhosus. Carneiro has showed the greatest abundance and diversity of bats (365 fragments). The species that presented the major number of fragments were Natulus struminaeus ( 138 fragments) and Pteronotus parnellii ( 134 fragments). This study presents the first record of the genera Lionycteris, Lonchorhina and Trachops from the Quaternary of South America. The species Pteronotus davyi does not occur in the recent fauna of Brazil, and may represent a local extinction. The diversity of Chiroptera found in Serra da Mesa is equivalent to that described for Bahia, which heretofore has the most abundant record for Quaternary bats from South America.